Frequency agile active microstrip antenna - Gautam A.K.; Vishvakarma B.R. (My University, 2025)
A new technique for designing the frequency agile microstrip antenna is presented. The frequency agility is achieved by symmetrical loading of two identical MOS capacitors at the radiating edge of the patch, in which the operating frequency of the rectangular microstrip antenna is electronically controlled by the bias voltage of MOS capacitors. Theoretical model for the antenna is developed using modal cavity model approach and results are also simulated with MOM based simulator. The tuning range is found to be 1.527 GHz (61.09%), which is much better than earlier reported data and the unloaded patch radiator. Antenna shows consistent return loss and radiation pattern for the entire tunable frequency range. © 2006 Wiley Periodicals, Inc.